Assessment of Imaging Modalities Against Liver Biopsy in Nonalcoholic Fatty Liver Disease: The Amsterdam NAFLD‐NASH Cohort - Troelstra, Marian A.; Witjes, Julia J.; Dijk, Anne‐Marieke; Mak, Anne L.; Gurney‐Champion, Oliver; Runge, Jurgen H.; Zwirs, Diona; Stols‐Gonçalves, Daniela; Zwinderman, Aelko H.; Wolde, Marije; Monajemi, Houshang; Ramsoekh, Sandjai; et al. (Journal of magnetic resonance imaging, 2021)
Background Noninvasive diagnostic methods are urgently required in disease stratification and monitoring in nonalcoholic fatty liver disease (NAFLD). Multiparametric magnetic resonance imaging (MRI) is a promising technique to assess hepatic steatosis, inflammation, and fibrosis, potentially enabling noninvasive identification of individuals with active and advanced stages of NAFLD. Purpose To examine the diagnostic performance of multiparametric MRI for the assessment of disease severity along the NAFLD disease spectrum with comparison to histological scores. Study Type Prospective, cohort. Population Thirty‐seven patients with NAFLD. Field Strength/Sequence Multiparametric MRI at 3.0 T consisted of magnetic resonance (MR) spectroscopy (MRS) with multi‐echo stimulated‐echo acquisition mode, magnitude‐based and three‐point Dixon using a two‐dimensional multi‐echo gradient echo, MR elastography (MRE) using a generalized multishot gradient‐recalled echo sequence and intravoxel incoherent motion (IVIM) using a multislice diffusion weighted single‐shot echo‐planar sequence. Assessment Histological steatosis grades were compared to proton density fat fraction measured by MRS (PDFFMRS), magnitude‐based MRI (PDFFMRI‐M), and three‐point Dixon (PDFFDixon), as well as FibroScan® controlled attenuation parameter (CAP). Fibrosis and disease activity were compared to IVIM and MRE. FibroScan® liver stiffness measurements were compared to fibrosis levels. Diagnostic performance of all imaging parameters was determined for distinction between simple steatosis and nonalcoholic steatohepatitis (NASH). Statistical Tests Spearman's rank test, Kruskal–Wallis test, Dunn's post‐hoc test with Holm‐Bonferroni P‐value adjustment, receiver operating characteristic curve analysis. A P‐value <0.05 was considered statistically significant. Results Histological steatosis grade correlated significantly with PDFFMRS (rs = 0.66, P < 0.001), PDFFMRI‐M (rs = 0.68, P < 0.001), and PDFFDixon (rs = 0.67, P < 0.001), whereas no correlation was found with CAP. MRE and IVIM diffusion and perfusion significantly correlated with disease activity (rs = 0.55, P < 0.001, rs = −0.40, P = 0.016, rs = −0.37, P = 0.027, respectively) and fibrosis (rs = 0.55, P < 0.001, rs = −0.46, P = 0.0051; rs = −0.53, P < 0.001, respectively). MRE and IVIM diffusion had the highest area‐under‐the‐curve for distinction between simple steatosis and NASH (0.79 and 0.73, respectively). Data Conclusion Multiparametric MRI is a promising method for noninvasive, accurate, and sensitive distinction between simple hepatic steatosis and NASH, as well as for the assessment of steatosis and fibrosis severity. Level of Evidence 2 Technical Efficacy 2